Media representations on mental illness: a scoping review protocol - Lacerda, Beatriz; Santos, Eduardo (Millenium - Journal of Education, Technologies, and Health, 2020)
Introduction: Media representations of mental illness have always been mostly negative, unfounded and have stigmatising effects on people with mental illness, especially considering the leading role that the media take in our lives. Objective: To identify what representations of mental illness are reported in the media. To map the associated media platforms; and finally, to identify reported mental illness. Methods: A scoping review will be conducted using the method proposed by the Joanna Briggs Institute. The selection of studies, extraction and synthesis of data will be carried out by two independent reviewers. Results: We foresee the inclusion of studies demonstrating incorrect and stigmatising media representations about mental illness. Improvements in these representations are expected, but with differences for each mental illness, with bipolarity, schizophrenia, and personality disorders being those with the worst representation, with frequent associations to crime and violence. Conclusion: It is expected that this review will reveal how mental illness persists in being a poorly represented theme in the various media spaces, from the written and digital press to artistic means such as cinema and video games. This review can also point to the social effects that come from these stigmatizing portraits, especially on people suffering from some mental illness.